2012
DOI: 10.1021/es204105h
|View full text |Cite
|
Sign up to set email alerts
|

High Rate Nitrogen Removal in an Alum Sludge-Based Intermittent Aeration Constructed Wetland

Abstract: A new development on treatment wetland technology for the purpose of achieving high rate nitrogen removal from high strength wastewater has been made in this study. The laboratory scale alum sludge-based intermittent aeration constructed wetland (AlS-IACW) was integrated with predenitrification, intermittent aeration, and step-feeding strategies. Results obtained from 280 days of operation have demonstrated extraordinary nitrogen removal performance with mean total nitrogen (TN) removal efficiency of 90% under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(61 citation statements)
references
References 39 publications
1
57
0
3
Order By: Relevance
“…Currently, it has been proven that CWs can serve as a cost-effective and promising alternative to conventional wastewater treatment methods for removing or reducing a wide variety of contaminant such as nitrogen, phosphorous, and chemical oxygen demand (COD) (Lin et al, 2002;Hu et al, 2012b;Li et al, 2013;Wang et al, 2013), and even antibiotics (Hijosa-Valsero et al, 2011;Liu et al, 2013b;Berglund et al, 2014;Chen et al, 2014) and ARGs (Liu et al, 2013b;Chen et al, 2014). However, most of the previous studies focus on the single removal of nitrogen, or phosphorous, or antibiotics by CWs.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, it has been proven that CWs can serve as a cost-effective and promising alternative to conventional wastewater treatment methods for removing or reducing a wide variety of contaminant such as nitrogen, phosphorous, and chemical oxygen demand (COD) (Lin et al, 2002;Hu et al, 2012b;Li et al, 2013;Wang et al, 2013), and even antibiotics (Hijosa-Valsero et al, 2011;Liu et al, 2013b;Berglund et al, 2014;Chen et al, 2014) and ARGs (Liu et al, 2013b;Chen et al, 2014). However, most of the previous studies focus on the single removal of nitrogen, or phosphorous, or antibiotics by CWs.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated that CWs are capable of removing a majority of environmental pollutants including nitrogen, phosphorous, chemical oxygen demand (COD) (Lin et al, 2002a;Hu et al, 2012;Li et al, 2013;Wang et al, 2013), and emerging contaminants such as antibiotics (Hijosa-Valsero et al, 2011;Berglund et al, 2014;Chen et al, 2015) and ARGs Chen et al, 2015). Their performance depends on the design parameters such as plant species, flow types, substrates, hydraulic loading rates, hydraulic retention time and applied pollutants loadings (Hijosa-Valsero et al, 2010;Hijosa-Valsero et al, 2011;Saeed and Sun, 2012;Weerakoon et al, 2013;Wu et al, 2014;Wu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recent developments of CW technology allows it to be able to treat high strength wastewater with robust organic and nutrients removal, with minimal construction and operating costs, by employing alum sludge as the main substrate and operating with a tidal flow strategy [13][14][15][16]. In order to function efficiently the anode compartment of a MFC must remain anaerobic while freely available oxygen at the cathode will combine with protons and electrons to complete the circuit.…”
Section: Introductionmentioning
confidence: 99%